Analisis Hubungan Tingkat Pengetahuan Ibu Hamil dengan Pemanfaatan Buku Kesehatan Ibu dan Anak - Rezkiani Kas, Sri; Nurul Fajriah Istiqamah (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2023)
The mother's lack of knowledge about the use of the Maternal and Child Health (KIA) book, which is still considered only as a health recording book for health workers, is an obstacle in forming mothers' health behavior regarding the importance of visiting the immunization series at posyandu. The aim of this research is to determine the relationship between the level of knowledge of pregnant women and the use of KIA books. The type of research used is a quantitative survey, with a correlative descriptive design. The results of the analysis test using the chi square test, namely that there was a relationship between the level of knowledge of pregnant women and the use of KIA books at the Pampang Community Health Center, obtained a p-value of 0.00 < 0.05.